Prospective Relations among Low-Income African American Adolescents’ Maternal Attachment Security, Self-Worth, and Risk Behaviors - Lockhart, Ginger; Phillips, Samantha; Bolland, Anneliese; Delgado, Melissa; Tietjen, Juliet; Bolland, John (Frontiers in Psychology, 2017)
This study examined prospective mediating relations among mother-adolescent attachment security, self-worth, and risk behaviors, including substance use and violence, across ages 13-17 in a sample of 901 low-income African American adolescents. Path analyses revealed that self-worth was a significant mediator between attachment security and risk behaviors, such that earlier attachment security predicted self-worth one year later, which in turn, predicted substance use, weapon carrying, and fighting in the third year. Implications for the role of the secure base concept within the context of urban poverty are discussed.